ANALISIS KOMUNIKASI KREATIF PADA VIDEO LIRIK LAGU “EGOSENTRIS” BAND ALKATERI - Rafa Radhitya Ghantari; Inko Sakti Dewanto (PT. Hasba Edukasi Mandiri, 2026)
The song “Egosentris” by Alkateri highlights the theme of personal ambition and the human tendency to focus attention on oneself. In the context of adolescent development, egocentric traits often emerge through the phenomena of the imaginary audience and personal fable, which can influence how individuals perceive themselves as well as others. In the digital era, this tendency becomes increasingly visible through self-presentation behaviors and reduced sensitivity toward empathy. A creative visualization of the song “Egosentris” serves as a reflective medium that helps audiences understand that egocentrism is not inherently negative, but requires balance to prevent it from developing into excessive individualism. This effort aligns with the principles of Good Health and Well-Being in SDG 3, which emphasizes the importance of mental health, emotional regulation, and self-awareness in daily life. Through a creative communication approach, the message conveyed in the song can be strengthened so that it encourages audiences to be more attentive to their emotional state while also maintaining healthy social relationships.